2006
DOI: 10.1002/elps.200500856
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive determination of carbohydrates labelled with p‐nitroaniline by capillary electrophoresis with photometric detection using a 406 nm light‐emitting diode

Abstract: p-Nitroaniline was explored as a derivatising reagent for UV absorbance detection of carbohydrates after separation by CE. This derivatising agent has three advantages: first, it has excellent water solubility; second, it has high molar absorptivity; and third, it is possible to obtain sensitive detection using a UV or blue light-emitting diode (LED) as the light source. The labelling reaction took less than 30 min to complete with high reaction yield. The separation process was modelled and optimised using an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Momenbeik et al [61] used the LED detection system coupled to CZE to determine carbohydrates derivatized with p-nitroaniline in food samples. Several parameters affecting the separation selectivity were studied using an artificial neural network able to predict mobilities including as response factor the quality of the final separation.…”
Section: Carbohydratesmentioning
confidence: 99%
“…Momenbeik et al [61] used the LED detection system coupled to CZE to determine carbohydrates derivatized with p-nitroaniline in food samples. Several parameters affecting the separation selectivity were studied using an artificial neural network able to predict mobilities including as response factor the quality of the final separation.…”
Section: Carbohydratesmentioning
confidence: 99%
“…Examination of the literature and recent experience with p-nitroaniline [20] suggested that small aromatic compounds containing a nitro group would have some absorbance in the near UV region and would be compatible with a UV LED detector. Through a comprehensive review of both scientific literature and commercial product catalogues, a number of nitro-aromatic compounds that had one or two ionisable sites (hydroxy and carboxylic acid groups) were selected.…”
Section: Probe Choicementioning
confidence: 98%
“…These are listed in Table 1. p-Nitroaniline (26) was said to have three advantages as a derivative for capillary electrophoresis (CE); it has excellent water solubility; second, it has high molar absorptivity; and third, it is possible to obtain sensitive detection using a UV or blue light-emitting diode (LED) as the light source [147]. Nine monosaccharides were separated by a CE system within 16 min using a 0.17 M boric acid buffer at pH 9.7.…”
Section: Aniline and Other Substituted Anilinesmentioning
confidence: 99%